PENGEMBANGAN BUKU PENGAYAAN ELEKTRONIK BERBASIS MULTIPLE INTELLIGENCES PADA MATERI SISTEM PENCERNAAN - Pratama, Een Suryani; Natalina. L, Mariani; Ahmad, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstarct: This research aims to develop an electronic enrichment book based on multiple intelligences on quality digestive system materials. This electronic enrichment book was developed based on indicators of multiple intelligences or multiple intelligences consisting of 9 types of intelligence that exist in each individual. This type of research is a development research using the ADDIE model. This research was carried out up to stage 3, namely the development stage. The instruments used for data collection are validation sheets, response questionnaire sheets. The trial was conducted on class XII students of SMAN 1 Pekanbaru. The results showed that the electronic enrichment book developed based on multiple intelligences was very feasible with an average score of 89.2. The usability analysis of the electronic enrichment book was obtained from the results of the first trial with an average value of 98 and the second trial with an average value of 97.1 with a very good category. This shows that the electronic enrichment book developed is very feasible to use and the application of the types of multiple intelligences or multiple intelligences can improve student learning outcomes.Key Words: Electronic Enrichment Book, Multiple Intelligences, Human Digestive System